Effect of Storage Time On Seed Viability of Cocoa (theobroma cacao l.) Variety Criollo - Effi Yudiawati; Tirana Lisna Sari; Setiono Setiono (Fakultas Pertanian Universitas Muara Bungo, 2022)
This research activity was carried out at the Laboratory of the Faculty of Agriculture, University of Muara Bungo Sungai Binjai and on Jl. Onion bone unit 3 Rimbo Mulyo Village, Kec. Rimbo Bujang Kab. Tebo, Jambi Province. This research activity was carried out for 2 months starting from 02 March - 02 April 2022. The aim of the research was to obtain information about whether storage duration affects the viability of cocoa seeds of the Criollo variety and to obtain optimal storage duration for the viability of cacao seeds of the Criollo variety. The design used in this study used a completely randomized design (CRD) with 6 treatments and 3 replications, the treatments were: P0 : 0 MSS (Week After Storage) = 0 Days After Storage, P1:1 MSS (Week After Storage) = 7 Days After Saving, P2 : 2 MSS (Week After Saving) = 14 Days After Saving, P3 : 3 MSS (Week After Saving) = 21 Days After Saving, P4 : 4 MSS (Week After Saving) = 28 Days After Saving, P5 : 5 MSS (Week After Save) = 35 Days After Save. Parameters observed were seed moisture content after storage (%), germination rate (%), normal sprouts (%), abnormal sprouts, dead sprouts (%), hypocotyl length, root length, shoot length, as well as supporting data (determining room temperature and humidity). Data obtained from observations were analyzed statistically using variance. If there is a significant effect, then proceed with the Duncan New Multiple Range Test (DNMRT) at 5% level. The results showed that the storage time of the criollo variety cocoa seeds on the viability of cocoa seeds had a very significant effect on the moisture content of the seeds after storage, germination, normal sprouts, dead shoots, long hypocotyl root length, shoot length, and had no significant effect on sprouts. abnormal. Treatments P0, P1 and P2 at 0 MSS to 2 MSS gave good treatment of the moisture content of the seeds after the storage period on the viability of the seeds on the effect of storage duration of the criollo variety cocoa seeds.